ФУНКЦИОНАЛЬНО-СЕМАНТИЧЕСКИЕ СВОЙСТВА ГЛАГОЛОВ СОСТОЯНИЯ В РЕЧИ ДИАЛЕКТОНОСИТЕЛЕЙ НА ТЕРРИТОРИЯХ СМЕШАННОГО ПРОЖИВАНИЯ РУССКИХ И УКРАИНЦЕВ - Tupikova, Nataliya Alekseevna; Bondarenko, Olga Vladimirovna (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2016)
The article considers the functional and semantic properties of verbs of existential status, that represent formation of one of the fragments of dialect lexicon of Russians and Ukrainians, members of the mixed Russian-Ukrainian families who live in the area of Don dialect distribution in Volgograd region. The analysis is focused on linguistic units possessing meanings of initial phase of being and existence, actual existence and cessation of existence. The authors summarize their observations on the specificity of vocabulary that was gained by collecting linguistic facts during dialectological expeditions, namely they are Russian and Ukrainian words with the above stated meanings that are used in everyday contact between representatives of closely related cultural communities settled in common area. The language specificity mirrors active transition and migration processes. Application of the field approach principles opened the way for presenting distinctions between nuclear and peripheral means of expressing state in the speech of informants, showing difference between central and polysegmental units, marginal and distal elements of the segments that are used in expressing sense in the utterance. It is viewed as reflection of interaction between culturally related Slavic languages (or their dialects) or contribution to a barrier-free natural language environment of dialect users who live in the communities with mixed Don Cossack and Ukrainians.